PERKEMBANGAN USAHA MIKRO, KECIL DAN MENENGAH (UMKM) DI PASAR MANONDA PALU - Nur Wanita (ISTIQRA, 2015)
This study aims to determine the development of Micro, Small and Medium Enterprises (SMEs) in the market Manonda Palu. To that end, it should also be recognized about the profile / picture of the UMKM`s doer. This study uses primary data and secondary data, where the primary data obtained from field observations and interviews, while the secondary data obtained from various publications both in the form of books, journals, research, document, and from the Internet. The method used is descriptive qualitative. Associated with the development of Micro, Small and Medium Enterprises (SMEs) in the market Manonda Palu, there is the difference between the micro, small, and medium enterprises. There are both slow and quite well development. The fast or slow development of UMKM at Manonda Palu market is influenced by internal and external factors which, internal factors among which are the limited availability of sources of funds (capital) and quality of human resources, while external factors of which are the existence of competition and business location, as well as supporting policy of the local government.